Sensory integration combined with interoceptive interventions for functional urinary incontinence in children: a case report - Ma, Lingshan; Zhang, Yuanxun; Yao, Songjun; He, Shuang; Li, Jie (Frontiers in Rehabilitation Sciences, 2025)
BackgroundFunctional urinary incontinence is prevalent among children and affects their daily life, psychology, and behavior. Although some behavioral therapies have been reported before, there is still no consensus on the treatment plan for functional urinary incontinence in children.Case informationThis case describes an 8-year-old girl presenting with urgency, urine leakage and frequent nocturnal enuresis. An 8-week sensory integration therapy combined with interoceptive training was implemented, followed by follow-up visits at 4 and 8 weeks after the intervention. Her urinary urgency and leakage symptoms gradually decreased over the 8 weeks of treatment and resolved completely by week 12. However, nocturnal enuresis persisted, suggesting the limited efficacy of sensory-based interventions in non-awake states.ConclusionsThe therapeutic effect of this case study indicates that interoceptive-sensory integration training has a positive effect on impaired bladder perception and voiding control during wakefulness and provides a new perspective for the evaluation and treatment of functional urinary incontinence. However, the improvement of enuresis by sensory enhancement still needs further research.